The Use and Misuse of Pleasure: Hadot contra Foucault on the Stoic Dichotomy Gaudium-Voluptas in Seneca - Matteo Johannes Stettler (Foucault Studies, 2022)
Chapter II of Foucault's The Care of the Self, 'The Cultivation of the Self,' is arguably one of the most controversial sections of the entire History of Sexuality. The diatribe over this chapter was initially mounted by Pierre Hadot's critical essay 'Reflections on the Idea of the 'Cultivation of the Self." Therein, Hadot objects to Foucault’s dissolution of the Stoic doctrinal antinomy between voluptas ('pleasure') and gaudium ('joy') and, thereby, to the relegation of the latter notion to the subordinate status of 'another form of pleasure', on the one side, and of Seneca himself to the problematic rank of a sort of Epicurean on the other. The present investigation aims to unveil this aspect of the Foucault-Hadot querelle as only a pseudo-controversy engendered by Seneca recurring to two different terminological registers throughout his writings: the so-called verbum publicum and the significatio Stoica.